Religiões afro-brasileiras em Belo Horizonte e região metropolitana: conflitos, violências e legitimação - Taisa Domiciano Castanha (2018)
This paper aims to describe and discuss the conflicts, violence and forms of legitimation of the Afro-brazilian religions in Belo Horizonte and the metropolitan region. Based on the cases of violence and conflicts involving two terreiros Manzo Ngunzo Kaiango in Belo Horizonte and Ilê Axé Sangô in Santa Luzia it was tried to think beyond the category of religious intolerance, operating the concept of symbolic violence of the sociologist Pierre Bourdieu, that allows to elucidate different facets of the violence suffered by the adherents of the Afro-brazilian religions. It has been realized that the conflicts and violence involving the Afro-brazilian religions embrace both neopentecostal churches and the State, as well as a complex intersection of prejudice and discrimination. The forms of reaction and legitimation of Afro-brazilian religions in the face of this scenario of violence and conflicts in the capital of Minas Gerais and its metropolitan region involve some strategies, separated into two axes in this work: the association of Afro-brazilian religions with the black movement and association of Afro-brazilian religions with the idea of culture.